What Every Indian Should Know Before Investing - S., Muruganandan (Indian Journal of Research in Capital Markets, 2023)
This is a book review of What Every Indian Should Know Before Investing authored by Mr. Vinod Pottayil. The author has crafted an informative and comprehensive guide for the Indian investors in a simple yet convincing language by considering both novice and seasoned investors. The book covered a wide range of investment options ranging from bank fixed deposit to cryptocurrencies. This book offered basic knowledge about the investment options to make informed decisions. The book emphasized to consider the pros and cons of each investment options before invest in. The book does not offer any advice to invest in a particular financial instrument. However, it attempts to educate the reader so that they can make sensible investing and money management decisions. The book concludes by emphasizing the importance of personal finance in everyone’s life. However, the author firmly believes that financial success can be possible only by educating the Indians to handle the financial products individually.